Concentration and temperature empirical relationships of the electrical conductivity of electrolyte solutions - Pavel Efimov; Andrey Kramarenko; Viktor Tomak (Вісник Харківського національного університету: Серія xімія, 2021)
We have considered the dependences of the specific (κ) and molar (Λ) electrical conductivity (EC) of aqueous electrolyte solutions on the molar concentration and temperature for sulfates of divalent metals (Mn, Co, Ni, Cu, Zn, Cd) in a wide concentration range at 5 – 35°C. To describe such systems we propose a modified cubic equation (MCE): κ = C∙c3k + Q∙c2k + L∙ck, where C, Q, L, k are empirical parameters, fixed parameter k = 0.5 has been considered as well. From the correlation between the calculated parameters we assume that two of them are sufficient. The maximum of specific EC (κm) and the corresponding concentration (cm) have been calculated. We also assume that the systems under study are isomorphic in the normalized coordinates (κ/κm via c/cm). For the dependences like κ = A∙cx + B∙cy it is shown that x = 1 is a good approximation over the generalized sample. Empirical dependences with y = 5/4 and y = 4/3 are also considered. It is shown that they give comparable results to MCE.